2020
DOI: 10.4155/bio-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an UHPLC–MS/MS Method for Extended Serum Steroid Profiling in Female Populations

Abstract: Aim: Quantitative endogenous steroid profiling in blood appears as a complementary approach to the urinary module of the World Anti-Doping Agency's Athlete Biological Passport Steroidal Module for the detection of testosterone doping. To refine this approach further, a UHPLC–MS/MS method was developed for the simultaneous determination of 14 free and 14 conjugated steroids in serum. Results: The method was validated for quantitative purposes with satisfactory results in terms of selectivity, linearity range, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The knowledge on how urine and serum androgen metabolites are connected may be of interest in anti-doping since quantification of endogenous serum steroids may be a complementary approach to the urinary steroid profile method in the future (Salamin et al, 2020). The monitoring of serum T may increase the likelihood to detect T intake in female athletes as serum T is superior compared to the urinary steroid profile (Handelsman and Bermon, 2019;Börjesson et al, 2020;Knutsson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The knowledge on how urine and serum androgen metabolites are connected may be of interest in anti-doping since quantification of endogenous serum steroids may be a complementary approach to the urinary steroid profile method in the future (Salamin et al, 2020). The monitoring of serum T may increase the likelihood to detect T intake in female athletes as serum T is superior compared to the urinary steroid profile (Handelsman and Bermon, 2019;Börjesson et al, 2020;Knutsson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that after 10 weeks of transdermal T application in healthy women, only 40% were identified as having atypical passport findings (Knutsson et al, 2020) even though their serum T levels were elevated to concentrations associated with performance enhancing effects (Hirschberg et al, 2020). As a supplementary method, the serum concentration of T, androstenedione and dihydrotestosterone may be co-monitored (Salamin et al, 2020) and subsequently there is an interest to understand the relation between the serum steroid concentrations and urinary excretion rate of the ABP metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending steroid profile analysis from urine to serum has been shown to be a promising complementary tool in anti‐doping analysis, and two analytical assays were reported that allow for quantifying the most relevant conjugated and unconjugated androgens. Salamin et al employed SPE to extract steroidal analytes from acidified serum, followed by concentration of the extract and subsequent LC‐MS/MS analysis 78 . Fourteen unconjugated steroids as well as 7 sulfo‐ and 7 glucurono‐conjugates were separated on a C‐18 analytical column (150 × 2.1 mm, 1.7 μm particle size) with 5‐mM ammonium formate (mobile phase A) and methanol (containing 5‐mM ammonium formate, mobile phase B), with T, EpiT, A, E, and EpiA being monitored as sulfates and glucuronides, while 5βAdiol was included as 3‐ and 17‐ O ‐glucuronide only and DHEA and norE as sulfate only.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Finally, the work of Nicoli and colleagues confirms that ultra high-performance LC (UHPLC)-tandem MS can provide reliable measurements of free and conjugated steroid concentrations in blood serum to complement those obtained by GC-MS/MS on free steroids in urine for the determination of the steroid profile required by WADA for the athlete biological passport. Furthermore, they illustrate the application of the method in the evaluation of females with mild hyperandrogenism and a group with normal circulating androgen levels, and suggest the clinical value of such an investigation as well as helping distinguish physiological outliers from sports cheats [11].…”
mentioning
confidence: 98%